2020
DOI: 10.1136/openhrt-2019-001203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preinterventional tricuspid regurgitation on outcome of MitraClip therapy in patients with severely reduced ejection fraction

Abstract: AimTo evaluate the impact of preinterventional moderate-to-severe functional tricuspid regurgitation (FTR) on early outcome after percutaneous edge-to-edge mitral valve repair (pMVR) with MitraClip procedures for functional mitral regurgitation (FMR) in patients with heart failure with reduced ejection fraction (HFrEF).Methods and resultsFrom January 2013 to December 2017, 80 patients with HFrEF (ejection fraction 22%±5.3%) and FMR (grade 3.0±0.36) underwent successful pMVR. The 3-year actuarial survival was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…We speculate that reduction of TR also compromises the effect of RV reverse remodeling, which is likely to be a process with a duration up to 6 months. 23 Studies with short TTE follow-up 13,[24][25][26] Our reduction rate of 25% after 6 months potentially reflects the effect of both acute and chronic reduction of TR. The less pronounced reduction of severe TR is likely explained by lack of structural reverse remodeling.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We speculate that reduction of TR also compromises the effect of RV reverse remodeling, which is likely to be a process with a duration up to 6 months. 23 Studies with short TTE follow-up 13,[24][25][26] Our reduction rate of 25% after 6 months potentially reflects the effect of both acute and chronic reduction of TR. The less pronounced reduction of severe TR is likely explained by lack of structural reverse remodeling.…”
Section: Discussionmentioning
confidence: 84%
“… 23 Studies with short TTE follow‐up interval (< 3 months) could therefore underestimate the benefit of TMVR regarding TR improvement. 13 , 24 , 25 , 26 Our reduction rate of 25% after 6 months potentially reflects the effect of both acute and chronic reduction of TR. The less pronounced reduction of severe TR is likely explained by lack of structural reverse remodeling.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Data about the role of concomitant TR in SMR patients are ambiguous, while again dedicated data of concomitant valvular pathology for PMR patients undergoing TMVr is unknown. While some authors found preprocedural severe TR as a predictor worsening prognosis after TMVr [77] others, including the large COAPT trial with echocardiographic core lab assessment, did not [25,78] [ Table 4]. We believe that moderate or severe TR in patients with SMR is tightly connected to the prevalent biventricular failure, thus a bystander.…”
Section: Smr Only Collectivementioning
confidence: 93%
“… 17 Studies were included if the articles met the following criteria: (i) reporting an association between RVD or tricuspid regurgitation and an outcome, either mortality or heart failure (HF) related hospitalization among patients with FMR; (ii) having at least 6 month follow‐up; (iii) controlling for other important covariates in multivariable survival analysis; (iv) having low risk of bias assessed by the Newcastle‐Ottawa scale (see Quality assessment section for more details). In the studies that reported an association of RVD or TR with outcomes among those with FMR mixed with primary MR, we contacted the authors of the studies for accessing data related to FMR 18,19 . Paediatric populations were excluded to minimize heterogeneity between studies.…”
Section: Methodsmentioning
confidence: 99%